Silicon-induced mitigation of salt stress in GF677 and GN15 rootstocks: insights into physiological, biochemical, and molecular mechanisms - Pouya Gharbi; Jafar Amiri; Nasser Mahna; Lotfali Naseri; MirHassan Rasouli Sadaghiani (BMC Plant Biology)
Abstract Salinity is a common environmental stress that disrupts physiological and biochemical processes in plants, inhibiting growth. Silicon is a key element that enhances plant tolerance to such abiotic stresses. This study examined the effects of silicon supplementation on physiological, biochemical, and molecular responses of GF677 and GN15 rootstocks under NaCl-induced salinity stress. The experiment was conducted in a greenhouse using a factorial design with two rootstocks, three NaCl concentrations (0, 50, and 100 mM), and three silicon levels (0, 1, and 2 mM) in a randomized complete block design with three replicates. Salinity significantly reduced growth parameters, including shoot and root fresh and dry weights, RWC, and photosynthetic activity, with GN15 being more sensitive to salt stress than GF677. Silicon supplementation, especially at 2 mM, alleviated NaCl-induced damage, enhancing biomass retention and RWC under moderate and high NaCl levels. Additionally, silicon reduced electrolyte leakage, lipid peroxidation, and hydrogen peroxide accumulation, suggesting a protective role against oxidative stress. Biochemical analyses showed that silicon increased the accumulation of osmolytes such as proline, soluble sugars, glycine betaine, and total soluble protein, particularly in GF677. Silicon also boosted antioxidant enzyme activities, mitigating oxidative damage. In terms of mineral nutrition, silicon reduced Na+ and Cl- accumulation in leaves and roots, with the greatest reduction observed at 2 mM Si. Gene expression analysis indicated that NaCl stress upregulated key salt tolerance genes, including HKT1, AVP1, NHX1, and SOS1, with silicon application further enhancing their expression, particularly in GF677. The highest levels of gene expression were found in plants treated with both NaCl and 2 mM Si, suggesting that silicon improves salt tolerance by modulating gene expression. In conclusion, this study demonstrates the potential of silicon as an effective mitigator of NaCl stress in GF677 and GN15 rootstocks, particularly under moderate to high salinity conditions. Silicon supplementation enhances plant growth, osmotic regulation, reduces oxidative damage, and modulates gene expression for salt tolerance. Further research is needed to assess silicon’s effectiveness under soil-based conditions and its applicability to other rootstocks and orchard environments. This study is the first to concurrently evaluate the physiological, biochemical, and molecular responses of GF677 and GN15 rootstocks to silicon application under salt stress conditions.